(untitled) (Acta Scientiarum. Animal Sciences, 2019)
The aim in this study was to evaluate the feeding behavior of goat kids fed diets containing peach palm meal replacing corn (0, 10, 40, 60, and 85 % on a dry matter basis). Thirty crossbred Boer kids, with 90 days old and initial body weight of 16.7 ± 3.5 kg were distributed in a completely randomized design with six replicates. Diets were daily supplied ad libitum to allow 10-20 % leftovers. Three collections were performed every 28 days. Diets were isoenergetics and isonitrogenous, composed of corn, soybean meal, peach palm meal, mineral supplement and Tifton 85 hay, with roughage: concentrate ratio of 30:70. There was a linear reduction in the intakes of dry matter (DM) and neutral detergent fiber (NDF) with a respective decrease of 35.7 % and 58.8 % comparing the diet with 85 % replacement and the control diet. The rumination and chewing times increased in diets with peach palm meal. The feeding and rumination rates decreased with reducing intakes of DM and NDF. The peach palm meal affects the feeding behavior and decreases the feed intake in response to palatability, fat and fiber composition, and it is recommended until 10 % replacing corn.